Effects of Glucose Oxidase Supplementation on the Growth Performance, Antioxidative and Inflammatory Status, Gut Function, and Microbiota Composition of Broilers Fed Moldy Corn - Qu, Wenhui; Liu, Jiaguo (Frontiers in Physiology, 2021)
Background Glucose oxidase is widely used as a livestock feed additive owing to its beneficial effects on growth performance and antioxidant activity. However, little is known about the effects of the enzyme on intestinal health. Methods To investigate the effects of glucose oxidase supplementation on the growth performance, intestinal function, and microbiota composition of broilers fed moldy corn, newly hatched Arbor Acres broilers were each randomly assigned to one of four groups, which were fed a basal diet (CON), a contaminated diet (10% moldy corn) (MC), a basal diet supplemented with 0.01% glucose oxidase (GOD), or a contaminated diet supplemented with 0.01% glucose oxidase (MCG). Results We found that the average weight gain (ADG) of the MC group was significantly lower than those of the CON and GOD groups, and there were no significant differences in ADG between the MCG group and the CON and GOD groups. Intestinal morphology results revealed irregularly arranged villi and microvilli in the ilea from the MC group, whereas those from the other three groups were aligned regularly. Tight-junction protein analysis showed that both ZO-1 expression and claudin-4 expression in the MC group were significantly lower than those in the other groups. Inflammation cytokines analysis showed lower serum concentration of interleukin-10, as well as its mRNA expression in the ileum of the MC group, when compared with those of the other groups. Additionally, we observed lower glutathione peroxidase and total superoxide dismutase activity and higher malonaldehyde concentration in the MC group than those in the MCG group. The α and β diversity of microbiota profiling indicated that the cecal microbiota in the MC group differed from those in the other three groups. Conclusion The results indicated that glucose oxidase supplementation was able to prevent the adverse effects from mycotoxin exposure on growth performance, antioxidant activity, inflammatory response, intestinal function, and microbiota composition in broilers. We suggested that glucose oxidase supplementation can be used in broilers to mitigate the adverse effects of moldy feed, and its benefits are due to its effect on intestinal microbiota composition.